Analysis of Pre-Service Science Teachers’ Ability to Integrate Technological Pedagogical Content Knowledge in Teaching Modules - Anggi Paramitha Sulfanjanti; Novi Ratna Dewi; Kuntoro Adi Juwanda (Jurnal Pendidikan Sains Indonesia, 2026)
The integration of technology in science learning requires teachers to possess strong technological pedagogical content knowledge (TPACK). This study aimed to analyze pre-service science teachers’ ability to integrate TPACK into teaching modules and to examine differences in TPACK integration between students from two teacher education institutions. A quantitative descriptive-comparative design was employed. The research sample consisted of 38 pre-service science teachers enrolled in the Professional Teacher Education Program (PPG), including 19 students from Semarang State University (UNNES) and 19 students from Universitas Tidar (UNTIDAR). Data were collected through documentation of teaching modules and assessed using a TPACK-based rubric covering seven components: TK, CK, PK, TCK, TPK, PCK, and TPACK. Data analysis involved descriptive statistics (mean and standard deviation) and inferential analysis using the Mann–Whitney test. The results showed that pre-service science teachers demonstrated good overall TPACK integration, with higher achievement in pedagogical and content-related components compared to technology-integrated components. Inferential analysis indicated no statistically significant difference in overall TPACK integration between PPG Science students from UNNES and UNTIDAR, despite slight descriptive variations across components. These findings suggest that strong pedagogical and content knowledge does not automatically ensure optimal technology integration. Therefore, systematic support and practice-oriented training are needed within teacher education programs to strengthen integrated TPACK development through authentic instructional products such as teaching modules